Comparative Analysis of Short-Chain Fatty Acids and the Immune Barrier in Cecum of Dahe Pigs and Dahe Black Pigs - Huijin Jia; Yuxiao Xie; Lanlan Yi; Wenjie Cheng; Guangyao Song; Wenzhe Shi; Junhong Zhu; Sumei Zhao (Animals)
The intestinal immune barrier is a developed and complex immune system, and there is a fine synergy between it and the induced immune response. Short-chain fatty acids (SCFAs) are the main metabolites of intestinal microbial fermentation. In the cecum of pigs, SCFAs not only provide energy for the host but also participate in regulating the function of the intestinal immune system. The purpose of this study was to explore the mechanism of SCFAs in the regulation of immune gene expression in porcine cecum. SCFAs content and mRNA expression levels of immune genes in cecum were detected, and Gene Ontology (GO) function annotation, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, Protein-Protein Interaction Networks (PPI) network construction, key gene identification, and correlation analysis were performed. The results showed that the content of SCFAs in the cecum of Dahe black pigs (DHB) was lower than that of Dahe pigs (DH). There were significant differences in mRNA expression of some immune genes between the two groups. GO functional annotation found terms related to cytokine activity and protein heterodimerization activity; the KEGG pathway was enriched in several pathways related to intestinal immunity. The PPI network identified Interleukin-6 (IL-6), Interleukin-8 (IL-8), Interleukin-10 (IL-10), Interleukin-17A (IL-17A), and Interleukin-18 (IL-18) as key proteins. The correlation analysis showed that acetic acid and valerate were closely related to the immune response. In this study, the differences in cecal short-chain fatty acids and the immune barrier between Dahe pigs and Dahe black pigs were compared, which provided a theoretical basis for improving the intestinal immunity of pigs.